The Effect of The Deep Learning Approach on The Learning Interest of Students in Grade IV of SDN Karang Anyar - Mohamad Hafidz Ikhsan; Aliet Noorhayati Sutisno; Nur Asyiah (FKIP - Universitas Riau, 2026)
Interest in learning is a key factor influencing student engagement in the learning process, particularly in Natural and Social Sciences (IPAS). However, teacher centered instruction has limited students' opportunities to actively participate in learning, resulting in low learning interest. This study aimed to analyze the effect of the Deep Learning approach on the learning interest of fourth-grade students in IPAS at SDN Karang Anyar. The study employed a quantitative approach using a pre-experimental method with a One Group Pretest-posttest design. The sample consisted of 30 students selected from one fourth-grade class. Data were collected through observation, questionnaires, and pretest-posttest assessments, and analyzed using the Shapiro-Wilk normality test, Normalized Gain (N-Gain), and the Paired Sample t-Test. The findings showed that the Deep Learning approach improved students' learning interest by promoting active engagement, exploration, discussion, problem-solving, presentations, and reflection. These findings indicate that the Deep Learning approach effectively enhances fourth-grade students' learning interest in IPAS.